Senescence of IPF Lung Fibroblasts Disrupt Alveolar Epithelial Cell Proliferation and Promote Migration in Wound Healing - Kaj E. C. Blokland; David W. Waters; Michael Schuliga; Jane Read; Simon D. Pouwels; Christopher L. Grainge; Jade Jaffar; Glen Westall; Steven E. Mutsaers; Cecilia M. Prêle; Janette K. Burgess; Darryl A. Knight (MDPI AG, 2020)
Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease marked by excessive accumulation of lung fibroblasts (LFs) and collagen in the lung parenchyma. The mechanisms that underlie IPF pathophysiology are thought to reflect repeated alveolar epithelial injury leading to an aberrant wound repair response. Recent work has shown that IPF-LFs display increased characteristics of senescence including growth arrest and a senescence-associated secretory phenotype (SASP) suggesting that senescent LFs contribute to dysfunctional wound repair process. Here, we investigated the influence of senescent LFs on alveolar epithelial cell repair responses in a co-culture system. Alveolar epithelial cell proliferation was attenuated when in co-culture with cells or conditioned media from, senescence-induced control LFs or IPF-LFs. Cell-cycle analyses showed that a larger number of epithelial cells were arrested in G2/M phase when co-cultured with IPF-LFs, than in monoculture. Paradoxically, the presence of LFs resulted in increased A549 migration after mechanical injury. Our data suggest that senescent LFs may contribute to aberrant re-epithelialization by inhibiting proliferation in IPF.